2019
DOI: 10.1080/23802359.2019.1667902
|View full text |Cite
|
Sign up to set email alerts
|

Complete mitochondrial genome sequence of lettuce pathogenic fungus, Fusarium oxysporum f. sp. lactucae 09-002

Abstract: Fusarium oxysporum is a famous plant pathogenic filamentous fungus. Here, we report the complete mitochondrial genome sequence of F. oxysporum f. sp. lactucae isolated from the lettuce field in Suwon area, Korea. Total length of the mitochondrial genome is 45,020 bp and it encodes 42 genes (15 protein-coding genes, two rRNAs, and 25 tRNAs). Nucleotide sequence of coding region takes over 32.7%, and overall GC content is 32.4%. Phylogenetic tree presented that F. oxysporum f. sp. lactucae 09-002 was clustered w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 15 publications
(25 reference statements)
0
3
0
Order By: Relevance
“…Instead, this phenomenon was found in genome studies focusing on intraspecific variations of insect, fungal, and marine invertebrate mitochondria. These include Laodelphax striatellus [ 93 , 94 ] and Nilaparvata lugens [ 95 97 ] belonging to the Delphacidae family; Fusarium oxysporum which is a fungal plant pathogen [ 98 , 99 ] and Apostichopus japonicus [ 100 ]. Because A. thaliana has a sufficient amount of sequencing data to construct chloroplast genomes, additional studies with more complete chloroplast genomes will provide a clear answer as to whether or not this phenomenon remains.…”
Section: Resultsmentioning
confidence: 99%
“…Instead, this phenomenon was found in genome studies focusing on intraspecific variations of insect, fungal, and marine invertebrate mitochondria. These include Laodelphax striatellus [ 93 , 94 ] and Nilaparvata lugens [ 95 97 ] belonging to the Delphacidae family; Fusarium oxysporum which is a fungal plant pathogen [ 98 , 99 ] and Apostichopus japonicus [ 100 ]. Because A. thaliana has a sufficient amount of sequencing data to construct chloroplast genomes, additional studies with more complete chloroplast genomes will provide a clear answer as to whether or not this phenomenon remains.…”
Section: Resultsmentioning
confidence: 99%
“…There were three fewer PCGs for three reasons: the smaller number of LAGLIDADG endonucleases, the absence of one endonuclease and a GIY-YIG endonuclease, and the presence of two additional PCGs—a hypothetical protein and a LAGLIDADG/HNH endonuclease. This particular configuration of PCGs is usually identified in other fungal mitogenomes; for example, two mitogenomes of Fusarium oxysporum (GenBank accessions are MN259514 and MN259515) display two completely different PCGs in each mitogenome [ 54 , 56 ]. There are also five fewer tRNAs because of the different configurations: tRNA-Asp, tRNA-Cys, tRNA-Ile, and two tRNA-Ser (also found in the mitogenome of the fungal symbiont of R. speculum [ 19 ]).…”
Section: Resultsmentioning
confidence: 94%
“…Interestingly, length of Ophiocordyceps sinensis mitochondrial genome is much larger than that of Fusarium mangifere but both were clustered in one clade with high bootstrap values (Figure 2(A)). The mitochondrial genome expansion in Aspergillus genus [16][17][18][19] and variable size of Fusarium mitochondrial genomes [18,20,21] suggested that mitochondrial genome expansion events may be occurred several times during evolution of fungal species. In addition, tree displayed two distinct clades in Colletotrichum genus, which is congruent with previous phylogenetic study [22] ( Figure 2).…”
Section: Koreanmentioning
confidence: 99%